A highly efficient supramolecular photoswitch for singlet oxygen generation in water. Issue 51 (2nd June 2016) - Liu, Guoxing; Xu, Xiufang; Chen, Yong; Wu, Xianjing; Wu, Huang; Liu, Yu
Abstract : Switching on/off singlet oxygen generation can be regulated upon irradiation with different wavelength light in a short period of time. Abstract : A series of water-soluble supramolecular assemblies were constructed from dithienylethene-modified permethyl-β-cyclodextrins and porphyrin derivatives, accompanied by a high FRET efficiency, and could be applied in the control of singlet oxygen generation in a 1% ethanol aqueous solution upon irradiation of different wavelength light. These findings will provide a feasible and convenient way to construct a potential photodynamic therapy material.